PENGARUH BEBAN KERJA TERHADAP PRODUKTIVITAS KERJA ROOM ATTENDANT DI KTM RESORT BATAM KEPULAUAN RIAU - Dayu Musdalifah; Syofia Achnes (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This study aims to determine: (1) To know the workload room attendant at KTM Resort Batam. (2) To know Work productivity room attendant at KTM Resort Batam. (3) To know the effect of workload on work productivity of room attendant at KTM Resort Batam. In this research the research method that I use is quantitative method with descriptive approach to examine the issues raised. The sample in this study as many as 8 people using the census method. While data collection techniques in this study using questionnaires, interviews and observation. By using Likert scale as a measuring tool to determine the short length of interval, multiple linear regression, validity test, reliability test and hypothesis test to determine the effect of variable x to y. Based on the results of research that has been done, there is a significant correlation or relationship between the workload with work productivity. The higher the workload the worse the productivity of work, this is due to lack of employees room attendant working at KTM Resort Batam. This research concludes that the workload received by KTM Resort Batam room attendant is very much, after the calculation of work load, the management must add 2 persons room attendant to reduce the workload of room attendant in KTM Resort Batam in order to achieve the Work Productivity good.Keywords: Workload, Work Productivit